Software-in-the-loop investigation of wake-vortex-encounter-response of identical multirotor pair with PX4 attitude controller - Wang, John Chung-Hung (2021)
Pairwise multirotor wake-encounter response studies with identical leader-follower unmanned aerial system (UAS) were conducted for a pair of Phantom 3 sized (∼1.2 kg) multirotor UAS with PX4 attitude controller used on the follower UAS. This is accomplished in the form of one-way coupled wake field from computational fluid dynamic (CFD) solution to Simulink software-in-the-loop (SITL) simulations. The study investigates resulting wake response as influenced by the substitution of idealized Lamb-Oseen vortex pair as stand-in for the CFD generated wake-vortex field produced by the leader UAS, as influenced by lateral positioning of the follower UAS relative to the track centerline, and as influenced by the follow distance between the encounter pair. The simulation results showed that the substitution of CFD with Lamb-Oseen vortex pair lacks flow along the vortex-axial direction, thus did not trigger the dynamic instability seen when the UAS was disturbed in all three rotational axis that was seen with CFD wake field. The dynamic instability of PX4 attitude controller in CFD wake field could be corrected by increasing the derivative gain for the yaw-rate. The investigations also showed that the maximum initial induced tilt angle, which is also the maximum value observed throughout, is highest when the follower UAS is positioned at a lateral offset equal to the distance between the wake-vortex core and the track centerline with the smallest follow distance feasible for the simulation to take place.